2016
DOI: 10.4322/rif.2016.005
|View full text |Cite
|
Sign up to set email alerts
|

WOOD AXIAL CHARACTERIZATION OF 32-YEAR-OLD Croton piptocalyx Müll. Arg. EUPHORBIACEAE

Abstract: This paper aims to characterize the wood anatomy of Croton piptocalyx. To carry out an investigation of axial variation, discussing it in a functional context, helping to increase knowledge about the species. Five randomly selected 32-year-old trees were felled at the Luiz Antonio Experimental Station, located in Luiz Antonio City, São Paulo state, Brazil. From stems, discs were cut from six different stem heights (stem base, 1 m, 2 m, 3 m, 4 m, and 5 m). For each disc, samples close to the bark were removed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…However, in 24-year-old Handroanthus vellosoi trees, it was found that the diameter of the vessels is smaller at the base of the tree, and greater at the heights of 1 and 2 m according to Longui et al (2017). Since the presence of narrower vessels at the base of the tree may be an indication of better efficiency in water transport due to pressure differences along the vessel elements (Assad et al, 2016) In this study, we also carried out correlations between basic density and anatomical features. We found that most important relationships were basic density with fiber wall thickness, fiber length and vessel frequency.…”
Section: Resultsmentioning
confidence: 99%
“…However, in 24-year-old Handroanthus vellosoi trees, it was found that the diameter of the vessels is smaller at the base of the tree, and greater at the heights of 1 and 2 m according to Longui et al (2017). Since the presence of narrower vessels at the base of the tree may be an indication of better efficiency in water transport due to pressure differences along the vessel elements (Assad et al, 2016) In this study, we also carried out correlations between basic density and anatomical features. We found that most important relationships were basic density with fiber wall thickness, fiber length and vessel frequency.…”
Section: Resultsmentioning
confidence: 99%
“…The authors also found an inverse relationship between hydraulic conductivity and mechanical resistance. The presence of narrower vessels at the stem base, acting as a bottleneck, is a pattern observed in several species, with the purpose of increasing water transport by pressure differences along the vessel elements, thus improving their hydraulic efficiency (Assad et al, 2016) and/or meeting the mechanical demands concerning tree support (Sette Jr. et al, 2012;Longui et al, 2017). A decrease in vessel diameter tends to form denser wood, with greater mechanical resistance, since vessel lumens represent empty spaces that can weaken the wood in terms of its mechanical properties (Baas et al, 2004).…”
Section: Influence Of Longitudinal Position On Physical and Anatomica...mentioning
confidence: 99%
“…In adult trees, cambium located at trunk base will produce wood with a characteristic typical of the age, while recently formed cambium located at the tree top will produce juvenile wood (Zobel & Sprague, 1998). The variations in cellular dimensions found along the tree trunk may be related to the typical radial pattern, where shorter and narrower cells occur in parts with younger wood (Assad et al, 2016).…”
Section: Influence Of Longitudinal Position On Physical and Anatomica...mentioning
confidence: 99%